The cytoplasmic membrane as a site of the primary effect of colicins on eukaryotic cells - Viklický, V; Smarda, J; Dráber, P; Pokorná, Z; Mach, J; Dráber, P (Folia biologica, 1979)
The effect of colicins E3 and K on mouse lymphoid cells was studied. Low doses of colicin E3, which were not toxic, inhibited profoundly the Con A-induced activation of lymphocytes while the Con A binding capacity of the treated cells was retained. The inhibitory effect of colicin E3 was also found when the homing of 51Cr-labelled lymph node cells to the lymph nodes of syngeneic recipients was studied, while the rate of redistribution of H-2 antigens on the surface of the lymphocytes was not changed by colicin E3 or colicin K. The findings suggest that the cytoplasmic membrane is the site of the primary effect of colicin E3 on eukaryotic cells.
Keywords: antigeny povrchové; Animals; Histocompatibility Antigens; Female; lymfocyty; histokompatibilní antigeny; ženské pohlaví; Fibroblasts; Lymphocyte Activation; aktivace lymfocytů; Thymidine; Mice; thymidin; receptory konkanavalinu A; fibroblasty; myši; Male; myši inbrední C57BL; Receptors, Concanavalin A; Colicins; koliciny; Lymphocytes; konkanavalin A; zvířata; mužské pohlaví; Antigens, Surface; buněčná membrána; Mice, Inbred C57BL; Concanavalin A; Cell Membrane